2021
DOI: 10.5343/bms.2020.0048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intra- and interspecific competition on periphyton biomass and growth performance of Holothuria scabra juveniles

Abstract: The effects of sea cucumber (Holothuria scabra) juvenile density and interspecific competition from the opisthobranch Stylocheilus striatus (SS) on periphyton biomass and growth performance of H. scabra (HS) were assessed. The number of H. scabra juveniles (15, 50, 100) in net enclosures (treatments HS15, HS50, and HS100) was varied and feeding activity of S. striatus was assessed at a density of 15 individuals per net enclosure (treatment SS15), and in co-culture with H. scabra (treatment HS15/SS15). A contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This situation could have been further exacerbated by the high number of competitors that recruited to the hapas , thereby increasing intra‐ and interspecific competition for food. S. striatus , for example, have been shown to consume up to ∼17.49 mg individual −1 day −1 (dry weight) of periphyton compared to ∼4.92 mg individual −1 day −1 (dry weight) of periphyton consumed by H. scabra juveniles (Gorospe et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation could have been further exacerbated by the high number of competitors that recruited to the hapas , thereby increasing intra‐ and interspecific competition for food. S. striatus , for example, have been shown to consume up to ∼17.49 mg individual −1 day −1 (dry weight) of periphyton compared to ∼4.92 mg individual −1 day −1 (dry weight) of periphyton consumed by H. scabra juveniles (Gorospe et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Post-settled sandfish juveniles are generally grazers and feed primarily on periphytic assemblages that develop on the inside surfaces of the hapa nets. These periphyton assemblages served as primary food source for sandfish juveniles throughout the 30-60-day ocean nursery culture period (Gorospe et al, 2020(Gorospe et al, , 2021Sinsona & Juinio-Meñez, 2019;Altamirano et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stocked yellowtail kingfish likely dispersed rapidly from release locations which is consistent with their pelagic life history, but there was little interaction between stocked fish and two large coastal artificial reefs. Gorospe et al (2021) showed the potential for experimental approaches to explore ecological interactions following release, particularly for relatively sessile benthic invertebrates. Translocation is a traditional management practice in certain shellfish fisheries (Spencer 2002) and has been implemented experimentally in others (Gardner et al 2015).…”
Section: Science Advances and The Development Of Enhancement Strategiesmentioning
confidence: 99%